2011
DOI: 10.1177/0163278711423937
|View full text |Cite
|
Sign up to set email alerts
|

Defining Physicians’ Readiness to Screen and Manage Intimate Partner Violence in Greek Primary Care Settings

Abstract: The current article aims to translate the PREMIS (Physician Readiness to Manage Intimate Partner Violence) survey into the Greek language and test its validity and reliability in a sample of primary care physicians. The validation study was conducted in 2010 and involved all the general practitioners serving two adjacent prefectures of Greece (n = 80). Maximum-likelihood factor analysis (MLF) was used to extract key survey factors. The instrument was further assessed for the following psychometric properties: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 31 publications
3
30
2
Order By: Relevance
“…Other strengths of this study are related to the content of the training program, which was designed to address existing knowledge/practice gaps of the Greek GPs [37] and the use of validated research instruments in the assessment of the study outcomes [39]. Most importantly, this study is among the few published studies, if not the first, that draws comparisons between practicing physicians and residents of the same specialty, in terms of IPV educational outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other strengths of this study are related to the content of the training program, which was designed to address existing knowledge/practice gaps of the Greek GPs [37] and the use of validated research instruments in the assessment of the study outcomes [39]. Most importantly, this study is among the few published studies, if not the first, that draws comparisons between practicing physicians and residents of the same specialty, in terms of IPV educational outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The PREMIS survey is a comprehensive and reliable self-administered measure of physician preparedness to manage IPV in four broad areas: (1) IPV background; (2) actual knowledge; (3) opinions; and (4) practice issues (self-reported management behaviours). The questionnaire has already been translated and validated in the Greek context by the authors of the current paper [39]. For the needs of the current study, 3 out of the 10 scales of the tool were employed, assessing participants’ actual IPV knowledge (10 items), perceived IPV knowledge (10 items) and perceived preparation to manage IPV at their clinical setting (14 items).…”
Section: Methodsmentioning
confidence: 99%
“…Maximum likelihood exploratory factor analysis was utilized to evaluate the psychometric properties of the adapted PREMIS for Pharmacists instrument. Results were compared to the original results by Short et al and to the results of the instrument adapted for use in two additional populations, health care students and Greek physicians [ 34 , 35 , 36 ]. Exploratory factor analysis was appropriate for this study as the measure being tested has only been utilized in three studies, two of which utilized an adaptation of the original instrument and found slightly different factor structures compared to the original study.…”
Section: Methodsmentioning
confidence: 99%
“…The Connor et al study demonstrated that the PREMIS scale can successfully be modified for use in other provider groups in addition to physicians. The second study translated the PREMIS instrument into another language (Greek) and tested it in a sample of primary care physicians in Greece [ 36 ]. The translated measure found all of the scales found in the original PREMIS study and the IPV screening scale found in the student study (see Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…25 PREMIS has previously been used in studies of physicians and health care students (medicine, dentistry, nursing, and social work) and has been found to be comprehensible, reliable, valid, and adaptable to health care providers beyond physicians. [25][26][27] The current study was part of a validation study of an adaptation of the PREMIS instrument specifically for pharmacy practice. These adaptations were made to address the unique practice characteristics, activities, and concerns of a community pharmacy practitioner.…”
Section: Study Questionnairementioning
confidence: 99%